Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1038/s41598-020-78441-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary organic acids and nature identical compounds on growth, immune parameters and gut microbiota of European sea bass

Abstract: A 71-day study was conducted to explore the effect of increasing dietary levels (0, 250, 500, 1000 mg kg feed−1; D0, D250, D500 and D1000, respectively) of a blend of microencapsulated organic acids (OA, specifically citric and sorbic acid) and nature identical compounds (NIC, specifically thymol and vanillin), on growth, intestinal immune parameters and gut microbiota (GM) of European sea bass juveniles reared under normal and subsequently suboptimal environmental conditions (high temperature, 30.0 ± 0.4 °C a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 92 publications
(119 reference statements)
5
35
0
Order By: Relevance
“…In this last-mentioned study, the authors revealed an increase in the abundance of Proteobateria, which has been proposed as a possible sign of gut microbiome imbalance in fish species. This is also in agreement with the observed increased taxa (Enterobacteriaceae) belonging to this phylum in sea bass gut microbiome, which experienced inflammatory gut mucosa after exposure to high temperature and low-oxygen condition (Busti et al, 2020b). In the present study, we did not observe a gut microbiome imbalance related to the lipid level tested, which remains within a general optimal requirement for this species.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this last-mentioned study, the authors revealed an increase in the abundance of Proteobateria, which has been proposed as a possible sign of gut microbiome imbalance in fish species. This is also in agreement with the observed increased taxa (Enterobacteriaceae) belonging to this phylum in sea bass gut microbiome, which experienced inflammatory gut mucosa after exposure to high temperature and low-oxygen condition (Busti et al, 2020b). In the present study, we did not observe a gut microbiome imbalance related to the lipid level tested, which remains within a general optimal requirement for this species.…”
Section: Discussionsupporting
confidence: 92%
“…In particular, while fish fed with L16 diet showed significant gut microbiome changes only at the autumn shift, parallel with a reduction in ecosystem diversity, for the L21 diet, both summer and autumn temperature shifts resulted in significant variations in the ecosystem. Temperature is known to modulate microbial diversity in animals especially in poikilothermic fish species (Sepulveda and Moeller, 2020); however, data explaining the interaction between diet and temperature changes in fish are scarce (Soriano et al, 2018;Busti et al, 2020b;Pelusio et al, 2020). Interestingly, among the few studies, which underlined the combined effect of temperature and dietary lipid level, Soriano et al (2018), in yellowtail kingfish, detected a reduced bacterial abundance and richness associated to a suboptimal low temperature and low dietary lipid level, suggesting that gut microbiome composition could maintain high relative abundance after the decrease in temperature only in the presence of appropriate nutritional conditions, pointing out the importance of optimal lipid level at low temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that farnesene play a significant role during oxidative injury of eukaryotic cells ( 63 ). Sorbic acid, a food preservative and feed additive ( 64 ), could inhibit the dehydrogenase system of bacteria preventing their reproduction ( 65 ). Evidence shows that diets with sorbic acid exert prebiotic properties, stimulating the development of beneficial bacteria taxa ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sorbic acid, a food preservative and feed additive ( 64 ), could inhibit the dehydrogenase system of bacteria preventing their reproduction ( 65 ). Evidence shows that diets with sorbic acid exert prebiotic properties, stimulating the development of beneficial bacteria taxa ( 64 ). Aspirin, which has antibacterial and anti-inflammation activities, could prevent colorectal cancer by inhibiting cyclooxygenase enzymes and maintain intestinal barrier integrity ( 66 , 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…(6-9 g kg −1 ), clearly enhanced the immune parameters of serum and mucus in sterlet sturgeon. According to previous reports, low doses of organic salts are involved in stimulating the growth of nonpathogenic bacteria and lactic acids, whereas the higher doses also have bacteriostatic effects, which can reduce the population of opportunistic bacteria(Busti et al, 2020). The exact mechanism of F I G U R E 4 Hind-gut morphological characteristics of sterlet sturgeon (Acipenser ruthenus).…”
mentioning
confidence: 99%